CRISPR-Cas9-based precise engineering of SlHyPRP1 protein towards multi-stress tolerance in tomato - Tran, Mil Thi; Son, Geon Hui; Song, Young Jong; Nguyen, Ngan Thi; Park, Seonyeong; Thach, Thanh Vu; Kim, Jihae; Sung, Yeon Woo; Das, Swati; Pramanik, Dibyajyoti; Lee, Jinsu; Son, Ki-Ho; et al. (Frontiers in Plant Science, 2023)
Recently, CRISPR-Cas9-based genome editing has been widely used for plant breeding. In our previous report, a tomato gene encoding HYBRID PROLINE-RICH PROTEIN 1 (HyPRP1), a negative regulator of salt stress responses, had been edited using a CRISPR-Cas9 multiplexing approach that resulted in precise eliminations of its functional domains, proline-rich domain (PRD) and eight cysteine-motif (8CM). We subsequently demonstrated that eliminating the PRD domain of HyPRP1 in tomatoes conferred the highest level of salinity tolerance. In this study, we characterized the edited lines under several abiotic and biotic stresses to examine the possibility of multiple stress tolerance. Our data reveal that the 8CM removal variants of HK and the KO alleles of both HK and 15T01 cultivars exhibited moderate heat stress tolerance. Similarly, plants carrying either the domains of the PRD removal variant (PR1v1) or 8CM removal variants (PR2v2 and PR2v3) showed better germination under osmosis stress (up to 200 mM Mannitol) compared to the WT control. Moreover, the PR1v1 line continuously grew after five days of water cut-off. When the edited lines were challenged with pathogenic bacteria of Pseudomonas syringae pv. tomato (Pto) DC3000, the growth of the bacterium was significantly reduced by 2.0-2.5-fold compared to that in WT plants. However, the edited alleles enhanced susceptibility against Fusarium oxysporum f. sp. lycopersici, which causes fusarium wilt. CRISPR-Cas9-based precise domain editing of the SlHyPRP1 gene generated multi-stress tolerant alleles that could be used as genetic materials for tomato breeding.